Palestine Connecting Resources to Preserve History - Rana A. Abdulrahman (16552596) (2023)
To enable the people to preserve their history is a job that the library has been doing for a long time. The library did this by preserving books and allowing access to materials related to history and culture in many forms. This access has been limited due to the Pandemic impact causing social distancing and closing libraries and heritage institutions. The Qatar National Library and Museum of Islamic Art library, as part of Doha City of Islamic Culture 2022, both worked simultaneously on a series of events related to Palestine. The events covered the history, culture and traditions of the Palestinian people. The two institutes believed it was an opportunity to connect through creating a library guide that includes all resources provided by both libraries. The collection included all rare books and manuscripts provided by the Museum of Islamic Art library and all print fiction and non-fiction print, audiobooks and other resources of Qatar National Library. This poster will share the efforts of the two institutes in connecting through sharing resources and with the community. The poster will include RFD codes linking to a virtual exhibition, the Palestine library guide, Opac, library catalogue and digitized manuscript. The poster will include stats about available resources, images from exhibitions and events and a timeline of content.